PERBANDINGAN PENYELESAIAN SENGKETA PEMILIHAN UMUM PRESIDEN DI INDONESIA DAN BRASIL : Comparison of Presidential General Election Dispute Resolution in Indonesia and Brazil - Billy Herlambang Rahmat Hidayat; Ninuk Wijiningsih (Faculty of Law, Universitas Trisakti, 2024)
Elections there are violations which are called general election disputes. In Indonesia, the dispute resolution regarding the Presidential election is resolved by several related institutions. In Brazil, disputes related to violations in the Presidential election are resolved by an authorized institution, namely the Superior Electoral Tribunal. The problems in this study are: What are the similarities and differences between the mechanisms for resolving presidential election disputes in Indonesia and Brazil, and whether the mechanisms for resolving presidential election disputes in Indonesia and Brazil are in accordance with the laws and regulations. This research is normative research, using secondary data, descriptive in nature, analyzed qualitatively, and deductive inference. The results are similarities related to rules set forth in laws and regulations in each country, having authorized institution in the presidential election dispute, the involvement of the judiciary and the decision is final and binding. The differences are related to the authorized institution in resolving presidential election disputes, the time of the presidential election dispute resolution process, and in terms of the results of decisions related to the presidential election dispute resolution mechanism. The conclusion is, Indonesia and Brazil have similarities and differences in resolving presidential election conflicts.